APPLICATION OF THERMAL ANALYSIS METHODS FOR THE COMPOSITION IDENTIFICATION OF EMULSIFIED FAT PRODUCTS - Budanina L.N.; Vereshchagin A.L.; Bychin N.V. (Техника и технология пищевых производств)
There is a need to develop methods for rapid determination of palm oil in dairy products because of the mass application of palm oil to replace milk fat. The possibility of applying thermal analysis methods to identify palm oil in emulsified fat products has been investigated in the given paper. The samples of sour cream of domestic and foreign production and the samples of mayonnaise of domestic production were used as the object of study. The study of composition of emulsified fat products was conducted using the methods of differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and differential thermal analysis (DTA). Thermal analysis methods (DSC, TGA/DTA) enable to identify the availability of palm oil in mayonnaise. DSC method enables to identify the presence of fats of non-dairy origin according to the melting temperature in the range of 30-50 deg. С in sour cream. TGA method can determine the mass fraction of fat by the residue weight after the water evaporation. The research conducted shows that five out of six investigated samples of sour cream are sour cream products. All test samples of olive mayonnaise do not have olive oil, and mayonnaise «Maheev» and «Persona» contain palm oil in their composition, and «Lies» and «Sloboda» mayonnaise contain sunflower oil.